RETINAL VASCULAR PERFUSION DENSITY MAPPING USING OPTICAL COHERENCE TOMOGRAPHY ANGIOGRAPHY IN NORMALS AND DIABETIC RETINOPATHY PATIENTS - Agemy, Steven A; Scripsema, Nicole K; Shah, Chirag M; Chui, Toco; Garcia, Patricia M; Lee, Jessica G; Gentile, Ronald C; Hsiao, Yi-Sing; Zhou, Qienyuan; Ko, Tony; Rosen, Richard B (Retina (Philadelphia, Pa.), 2015)
To describe a new method of retinal vascular perfusion density mapping using optical coherence tomography angiography and to compare current staging of diabetic retinopathy based on clinical features with a new grading scale based on perifoveal perfusion densities. A retrospective review was performed on subjects with diabetic retinopathy and age-matched controls imaged with a spectral domain optical coherence tomography system (Optovue XR Avanti, Fremont, CA). Split-spectrum amplitude-decorrelation angiography (SSADA) generated optical coherence tomography angiograms of the superficial retinal capillaries, deep retinal capillaries, and choriocapillaris. Skeletonized optical coherence tomography angiograms were used to create color-coded perfusion maps and capillary perfusion density values for each image. Capillary perfusion density values were compared with clinical staging, and groups were compared using analysis of variance and Kruskal-Wallis analyses. Twenty-one control and 56 diabetic retinopathy eyes were imaged. Diabetic eyes were grouped according to clinical stage. Capillary perfusion density values from each microvascular layer were compared across all groups. Capillary perfusion density values were significantly lower in nearly all layers of all study groups compared with controls. Trend analysis showed a significant decrease in capillary perfusion density values as retinopathy progresses for most layers. Quantitative retinal vascular perfusion density mapping agreed closely with grading based on clinical features and may offer an objective method for monitoring disease progression in diabetic retinopathy.